The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.3109/10731197709118683
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies with L-Asparaginase Bound to Implantable Bovine Collagen Heterografts: A Potential Long-Term, Sustained Dosage, Antitumor Enzyme Therapy System

Abstract: In this study, L-Asparaginase has been bound to collagen heterografts derived from carotid bovine arteries. The immobilization procedure utilizes both non-covalent and covalent interactions to fix the enzyme. Binding of the enzyme to the graft material was shown to the pH dependent, with optimum binding occurring at pH 6.0 and pH 8.5. Amidohydrolysis by the bound enzyme exhibited zero-order kinetic behavior at substrate saturating conditions. Total apparent asparaginase activity expressed by the grafts as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The modification or immobilization of the enzyme not only reduced its immunity and toxicity to humans but also greatly improved its resistance to proteolysis in comparison with native ASNase. Some attempts have been made to prepare insoluble, matrix‐supports for ASNase immobilization, such as collagen,5 CM‐cellulose,6 polyacrylamide,7 poly (2‐hydroxyethyl methacrylate) gels,8, 9 and PEG–BSA hydrogels 10. This type of derivative may be appropriate for extracorporeal devices in the clinical treatment of ALL.…”
Section: Introductionmentioning
confidence: 99%
“…The modification or immobilization of the enzyme not only reduced its immunity and toxicity to humans but also greatly improved its resistance to proteolysis in comparison with native ASNase. Some attempts have been made to prepare insoluble, matrix‐supports for ASNase immobilization, such as collagen,5 CM‐cellulose,6 polyacrylamide,7 poly (2‐hydroxyethyl methacrylate) gels,8, 9 and PEG–BSA hydrogels 10. This type of derivative may be appropriate for extracorporeal devices in the clinical treatment of ALL.…”
Section: Introductionmentioning
confidence: 99%
“…One of the methods for L‐ASNase immobilisation is physical adsorption on the surface of carriers. In this paper, insoluble matrix supports have been used for enzyme immobilisation such as carboxymethyl cellulose [7], collagen [8], poly(2‐hydroxyethyl methacrylate) gels, polyacrylamide [9, 10], and polyethylene glycol and bovine serum albumin hydrogels [11]. Another way for enzyme immobilisation is physical trapping the enzyme in liposomes [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the immobilized enzyme not only reduces toxicity, but also greatly improved resistance to proteolysis compared to native L-asparaginase (Zhang et al, 2004;Ghosha et al, 2011). Attempts were made for the preparation of insoluble matrix supports such as collagen (Jefferies et al, 1977), carboxy methyl cellulose (Hasselberger et al, 1970), polyacrylamide and poly (2-hydroxyethyl methacrylate) gels (O'Driscoll et al, 1975) derivatives bioconjucated with L-asparaginase for use in cancer therapy. That said, enzyme immobilization has attracted great interest by chemists and biochemists for its wide application in academic research and industrial processes (Mahmoud and Helmy, 2009;Shafei et al, 2015).…”
Section: Introductionmentioning
confidence: 99%